Penanganan permasalahan sampah di TPA Tlekung Kota Batu - Wati, Amelia Rochima (Maliki Interdisciplinary Journal, 2024)
This research has been undermined by the problems that have occurred in the TPA village of Tlekung city of Batu. Waste is a remnant of the everyday mass of household garbage, organic, inorganic and hazardous waste of such kinds. Many impacts will be achieved if one of the impacts is not disposed of, that is, if it is continuously collected or accumulated and there is no disposal, it will result in environmental damage, underground water pollution, air to the flow of waste into the river, and the release of unpleasant odors that can disturb society. This research is aimed at finding out how to solve the problem of garbage smell that exists in TPA Tlekung city of Stone. This research uses literation methods, the problem that is in the TPA tlekung that is the smell of trash that is present in Tpa, from the presence of such smell makes the town unbearable with its stinginging smell which makes uncomfortable people around. From the problem Pj Mayor of the City of Batu Aries paewai come down hands to deal with the smell of garbage that is in the TPA village Tlekung. With a waste disposal program with a reuse, reduce, and recycle system (TPS 3R) in every village and village, local residents participated in the waste treatment program made by the municipal governor of Batu.